'I want every minute to be worthwhile now': The views and experiences of people living with dementia and their care partners about returning to in-person group meetings after COVID-19 lockdown restrictions. (November 2022) - Kelly, Siobhán; Bushell, Sophie; Innes, Anthea
COVID-19 and the resulting limitations on freedom of movement has been difficult for many, including individuals living with dementia and those who provide support and care. In the summer of 2021, England's national lockdown measures eased, and regulations were amended to allow indoor social gatherings. With this enabling a return to in-person meetings, this study explored the experiences of people living with dementia and current and former care partners who had previously attended groups at Salford Institute for Dementia (UK). Two phases of research were conducted. In the first phase, during the summer of 2020, telephone interviews were utilised to ask participants ( n = 13) about their views of re-engagement and how the in-person groups might be best reintroduced. Phase two began in the summer of 2021, where mood questionnaires ( n = 10) were administered and observations conducted to explore how participants experienced the return to in-person meetings. Thematic analysis resulted in the construction of three overarching themes: planning for and the reality of transitioning; safety versus autonomy; and tensions and complexities of life in the 'new normal'. Despite initial concerns about their reintegration into the community, participants all enjoyed resuming in-person meetings. An inclusive and consultative approach to re-engagement allowed all participants to feel valued, safe, and informed about their return to campus. However, individuals living with dementia and care partners experienced the transition to re-engagement in different ways and their perceptions shifted over time. We therefore highlight the complexities of responding to different perceptions of risk and safety, while also promoting engagement and inclusivity after a period of social isolation. In this paper, we consider implications for the re-integration of individuals with dementia and their care partners into in-person social groups and propose further avenues for research.